Imaging Pulmonary Foreign Body Reaction Using [(125)I]iodo-DPA-713 SPECT/CT in Mice - Sanchez-Bautista, Julian (Mol Imaging Biol, 2019)
PURPOSE: Foreign body reactions elicit granulomatous inflammation composed of reactive macrophages. We hypothesized that [(125)I]iodo-DPA-713 single-photon emission computed tomography (SPECT), a low-molecular-weight pyrazolopyrimidine ligand selectively trapped by phagocytes, could be used to detect foreign body reactions in a murine model. PROCEDURES: C57BL/6 mice intratracheally inoculated with dextran beads, which developed foreign body lesions, were imaged after injection of [(125)I]iodo-DPA-713 or DPA-713-IRDye800CW using SPECT and optical imaging, respectively. RESULTS: Foreign body lesions were clearly observed in the lungs of the dextran-treated mice on computer tomography imaging and demonstrated significantly higher [(125)I]iodo-DPA-713 uptake compared with control animals (p < 0.01). Ex vivo studies demonstrated granulomatous reactions in the lungs of dextran-treated mice and localization of DPA-713-IRDye800CW at the diseased sites confirming the imaging findings. CONCLUSION: Radioiodinated DPA-713 may be used as a noninvasive biomarker for the detection of pulmonary foreign body reactions.